2016
DOI: 10.1017/s0144686x16001380
|View full text |Cite
|
Sign up to set email alerts
|

‘You're not really a visitor, you're just a friend’: how older volunteers navigate home visiting

Abstract: At the intersection of increasing social support needs due to population ageing and the promotion of older age as a time of contribution and social connection, volunteering is an important focus with advantages for older people. One service that addresses both these imperatives is home visiting services. Home visiting services connect home visitors with isolated older people. To examine how older people navigate volunteering for a home visiting service, six visitors were interviewed and the interviews were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Cameron et al (2020) reported that for older people volunteering gave them structure and purpose to the day and for the older person in receipt of the volunteer activity they benefited from having someone who could really take the time to talk and listen. Lilburn et al (2018), exploring the experiences of six adults aged 68–90 who volunteer for home visiting, reported that while volunteers positioned the activity as ‘work and a responsibility’ there were also narratives of shifting these obligations into mutual connections that benefit both the volunteer and those they visit. These examples highlight that the ceasing of volunteering activities is likely to have had a detrimental impact on both groups.…”
Section: Health and Wellbeing Effects Of Volunteering On Older Peoplementioning
confidence: 99%
“…Cameron et al (2020) reported that for older people volunteering gave them structure and purpose to the day and for the older person in receipt of the volunteer activity they benefited from having someone who could really take the time to talk and listen. Lilburn et al (2018), exploring the experiences of six adults aged 68–90 who volunteer for home visiting, reported that while volunteers positioned the activity as ‘work and a responsibility’ there were also narratives of shifting these obligations into mutual connections that benefit both the volunteer and those they visit. These examples highlight that the ceasing of volunteering activities is likely to have had a detrimental impact on both groups.…”
Section: Health and Wellbeing Effects Of Volunteering On Older Peoplementioning
confidence: 99%
“…Training and orientation sessions provided by volunteer organizations are also critically important in shaping prospective volunteers' image of their clients and their needs (Holden, 1997;Jensen, Lou, Aagaard, & Vaeggemose, 2017;Kramer, 2010;Lilburn, Breheny, & Pond, 2018;McCorkle et al, 2009;Musick & Wilson, 2008;Thompson, Valenti, Siette, & Priebe, 2016). The content of training is reported to generate concern and trepidation among the prospective volunteers (Greenwood et al, 2016).…”
Section: Application Of the Role Commitment Model Other's Identitymentioning
confidence: 99%
“…In studies of the relationships created in home visiting services ( e.g. Fournier, 2018; Lilburn et al ., 2018), a central characteristic of the relationship is that the older volunteers adopt a professional approach in their role as visitors. Through scheduled visits and volunteer courses they feel equipped to create a room of trust for an isolated older person.…”
Section: Blurry Volunteeringmentioning
confidence: 99%
“…The Danish welfare state is increasingly dependent on volunteers who are intended to help solve future welfare challenges (La Cour and Højlund, 2008). Of particular interest in this regard is the challenge of an ageing society consisting of an increasing number of older people who need care (Lilburn et al ., 2018).…”
Section: Introduction and Aimsmentioning
confidence: 99%
See 1 more Smart Citation